Enhancing Digital Education: A Model for Effective Mobile Learning Implementation in Malaysian Higher Education - Murad, Roslinda; Jusoh, Zeti Suzila Mat; Rahman, Benazir Tanjung Fatkur (Journal of Ecohumanism, 2024)
This study investigates the implementation of mobile learning (m-learning) services in the smart environment at Kolej Poly-Tech MARA (KPTM) in Malaysia, focusing on establishing effective practices for digital education. Despite the potential of m-learning as an educational tool, its adoption in Malaysia remains limited, with the COVID-19 pandemic highlighting the need for innovative approaches to learning. The research employs a mixed methods approach, gathering quantitative data from 365 respondents, including students, lecturers, and administrators, through Likert-scale questionnaires distributed via Google Forms. Qualitative data were obtained through interviews with 10 selected participants. The study identifies existing practices in m-learning, explores its benefits, and examines challenges faced during implementation. Utilizing descriptive analysis, one-way ANOVA, Independent T-Test, and Regression Correlation, the findings reveal a positive perception of m-learning among stakeholders, alongside challenges related to infrastructure and training. The primary contribution of this research is the development of a model of good practice that provides guidelines for KPTM and other higher education institutions aiming to enhance the quality of mobile learning services. This model emphasizes the importance of accessibility, professional development, and stakeholder collaboration, positioning KPTM toward a more effective digital education landscape. Overall, the study underscores the critical role of m-learning in fostering flexible and engaging learning environments while addressing the barriers to its implementation in Malaysia.